Blind subjects implanted with the Argus II retinal prosthesis are able to improve performance in a spatial-motor task - Ahuja, A K; Dorn, J D; Caspi, A; McMahon, M J; Dagnelie, G; daCruz, L; Stanga, P; Humayun, M S; Greenberg, R J (British journal of ophthalmology, 2011)
Background/aimsTo determine to what extent subjects implanted with the Argus II retinal prosthesis can improve performance compared with residual native vision in a spatial-motor task.MethodsHigh-contrast square stimuli (5.85 cm sides) were displayed in random locations on a 19″ (48.3 cm) touch screen monitor located 12″ (30.5 cm) in front of the subject. Subjects were instructed to locate and touch the square centre with the system on and then off (40 trials each). The coordinates of the square centre and location touched were recorded.ResultsNinety-six percent (26/27) of subjects showed a significant improvement in accuracy and 93% (25/27) show a significant improvement in repeatability with the system on compared with off (p<0.05, Student t test). A group of five subjects that had both accuracy and repeatability values <250 pixels (7.4 cm) with the system off (ie, using only their residual vision) was significantly more accurate and repeatable than the remainder of the cohort (p<0.01). Of this group, four subjects showed a significant improvement in both accuracy and repeatability with the system on.ConclusionIn a study on the largest cohort of visual prosthesis recipients to date, we found that artificial vision augments information from existing vision in a spatial-motor task.Clinical trials registry noNCT00407602.